Telaah terhadap Status dan Kedudukan Perempuan dalam Islam Perspektif Mubadalah - Na'im, Arroyan; Bagus Kusumo Hadi; Hairil Adi Saputra; Sri Jati Ratna Sari; Dino Gautman Raharjo (Institut Agama Islam Negeri Metro, 2024)
The testimony of women is the focus, with scholars holding diverse views regarding the eligibility of women as witnesses. In some contexts, such as muamalah, women are allowed to testify, while in fiqh jinayah, their testimony is strictly prohibited. It is essential to interpret Quranic verses using a broader and more comprehensive approach, connecting them to the conditions of women during the time of the Quran’s revelation. QS Al-Baqarah (2): 282 should be seen as progress, as it acknowledges the role of women as witnesses, a recognition that was previously absent during the Jahiliyyah period. This verse affirms the status of women as autonomous legal subjects, reflecting humanitarian values. The interpretation of this verse should be contextual, not merely literal, and adapted to the changing times based on the mubadalah perspective. This study employs a qualitative descriptive method and literature review techniques to collect primary and secondary data. The aim is to answer the posed questions and explain the status of women from a mubadalah perspective. QS Al-Baqarah (2): 282 is viewed as progress because it acknowledges women as witnesses, even though at that time, they were largely confined to the domestic sphere. The interpretation of this verse must be analyzed historically and contextually, considering social changes that have opened access for women to various public domains. Individual competence and understanding, rather than gender, should be the basis for evaluating testimony, as recognized by classical and contemporary scholars. Thus, the equal value of women's testimony with that of men aligns with the principles of justice and humanity in Islam